OXIGENAÇÃO POR MEMBRANA EXTRACORPÓREA (ECMO) NO TRATAMENTO DE PACIENTES COM COVID-19: REVISÃO SISTEMÁTICA: ECMO no tratamento de pacientes com COVID-19 - Costa Araujo, Amanda (2022)
Introduction: The use of Extracorporeal Membrane Oxygenation (ECMO) has been studied in the treatment of patients with COVID-19, since this therapy has already shown favorable results in the treatment of acute respiratory failure of viral etiology, as in H1N1 influenza. Objectives: Analise the effectiveness of using ECMO in patients with severe acute respiratory failure caused by COVID-19. Material and Methods: For this purpose, a systematic literature review was carried out using the PICO structure (Patient, Intervention, Comparison and “Outcome”) to formulate the guiding question. Controlled descriptors (DECS) were used to select the articles: ("Extracorporeal Membrane Oxygenation *" OR ECMO OR "Extracorporeal Life Support *" OR ECLS) and ("COVID *" OR Coronavirus OR "SARS *"). The searches were made in the COCHRANE LIBRARY, PubMed, EMBASE and CINAHL databases. Revisions, editorials, congress abstracts and study protocols were excluded. The variables analyzed were: The benefits and safety of this treatment, as well as whether there was a reduction in the mortality rate, contraindications and risks with this treatment. Results: After consulting the databases, 292 articles were identified using the descriptors mentioned above, of which 11 were included in this study after the selection process. The patients who needed ECMO were predominantly elderly and had the following risk factors: systemic arterial hypertension (SAH), meningococcal disease (DM) and obesity. The main complications found were hemorrhagic and thromboembolic. Finally, the mortality rate varied considerably between studies and it was possible to observe a significant decrease among patients who received this treatment. Discussion: The main results of this systematic review showed that the patients in this study were predominantly elderly and had underlying diseases mainly systemic arterial hypertension (SAH), meningococcal disease (DM) and obesity. Conclusion: Therefore, as it is a recently studied health condition, it is necessary that further studies be conducted to confirm the effectiveness of ECMO in patients with COVID-19.